O “MENIR” DOS SETE (MONFORTE): DADOS ARQUEOLÓGICOS - Rocha, Leonor (2018)
The work carried out in Menir dos Sete (Sete 1), are included in the research project that the authors have been developing in Monforte district since 2011. The main purpose was to verify if really was a menhir, or a natural monolith, and If there were associated structures and / or stratigraphies that could attest to its use in the course of Recent Prehistory.